Are we Missing Barrett's Esophagus in Our Busy Endoscopy Practice? Improving Detection - Dutta, Amit Kumar (Journal of Digestive Endoscopy, 2022)
Barrett's esophagus (BE) denotes the replacement of stratified squamous epithelium of esophagus by columnar epithelium. It is associated with a significantly increased risk of esophageal adenocarcinoma and hence patients with BE are advised endoscopic surveillance for early detection of dysplastic and neoplastic lesions. Esophageal cancer is the sixth most common cancer in terms of incidence and mortality in India. Around 15 to 25% of esophageal cancers are adenocarcinoma. BE is likely to be an important precursor of esophageal adenocarcinoma and we may be missing patients with BE in our busy endoscopy practice. The detection of BE may be improved by identifying high-risk groups, performing thorough endoscopic examination, and applying newer imaging techniques. The high-risk group includes patients with chronic gastroesophageal reflux disease, obesity, smoking, etc. During endoscopic examination, a careful assessment of the gastroesophageal junction and identification of important landmarks such as gastroesophageal junction and Z line are essential to detect BE. Management of BE depends on the detection of dysplasia and for this four quadrant mucosal biopsy is recommended every 1 to 2 cm. However, random biopsy samples only a small area of mucosa and advanced technologies for real-time detection of dysplasia and neoplasia may overcome this limitation. In this review, we discuss the current scenario of BE in India and ways to improve the detection of BE including dysplastic lesions.
Keywords: Barrett's esophagus; dysplasia; image enhanced endoscopy; risk factors